2021
DOI: 10.1088/1361-6587/abe83c
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of laser wake phase velocity generates high-power broadband Cherenkov signal

Abstract: As a femtosecond terawatt laser pulse propagates along a positive density gradient within a stratified plasma column, it drives a low-frequency electromagnetic wake wave, the period of electron fluid oscillations in the wake gradually shrinking. Phase velocity of the wake promptly exceeds the vacuum speed of light, setting in near-forward emission of terahertz Cherenkov radiation. As the wake accelerates further, the Cherenkov emission ray rotates by 180∘. Emission from a given plasma locality is sustained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…Mention, the phase velocity passes through a singlularity at τ = L/c, then reverses and becomes negative afterwards. It has been recently shown that this reversal can be used to generate high-power broadband Cherenkov signal [23]. Here, instead we discuss a narrow band emission at plasma frequency harmonics.…”
mentioning
confidence: 99%
“…Mention, the phase velocity passes through a singlularity at τ = L/c, then reverses and becomes negative afterwards. It has been recently shown that this reversal can be used to generate high-power broadband Cherenkov signal [23]. Here, instead we discuss a narrow band emission at plasma frequency harmonics.…”
mentioning
confidence: 99%